CORRELATION BETWEEN QUALITY OF LIFE WITH INTERLEUKIN-6 SERUM LEVELS INCHRONIC KIDNEY DISEASE PATIENTS UNDERGOING REGULAR HEMODIALYSIS - Ahmad Muhar, Habibah Hanum Nasution & Alwi Thamrin Nasution (International Journal of Research Science and Management, 2020)
The morbidity and mortality rates of patients with chronic kidney disease (CKD), who undergo regular hemodialysis are still high. Cytokine levels, such as IL-1, IL-6, and TNF-α are often found to be increased in hemodialysis patients. The Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36) has been widely used in evaluating the quality of life of patients suffering from chronic diseases. This study aims to determine the level of quality of life and serum interleukin-6 levels in regular hemodialysis patients. This study was an observational cross-sectional method which was carried out at the hemodialysis center at the General Hospital. H. Adam Malik (RSUP HAM) during February - April 2017 with a sample of 45 people who were collected consecutively. Samples were patients with chronic kidney failure who had undergone regular hemodialysis at RSUP HAM. The majority of subjects causing chronic kidney disease were hypertensive nephropathy in 25 patients (55.6%). Serum IL-6 laboratory examination showed a mean value of 9.02. Based on our SF-36 questionnaire, we found a mean value below 50 for all scales examined in the study samples. Spearman correlation test between IL-6 with each scale from the SF-36 questionnaire found all parameters produced positive correlation data (p <0.05). We conclude that there is a significant correlation between IL-6 levels and the quality of life of Chronic Kidney Disease patients undergoing hemodialysis.